LOFAR observations of decameter carbon radio recombination lines towards Cassiopeia A - Salas, P; Oonk, J; van Weeren, R; Salgado, F; Morabito, L; Toribio, M; Emig, K; Röttgering, H; Tielens, A (Oxford University Press, 2017)
We present a study of carbon radio recombination lines towards Cassiopeia A using low frequency array (LOFAR) observations in the frequency range 10–33 MHz. Individual carbon α lines are detected in absorption against the continuum at frequencies as low as 16 MHz. Stacking several Cα lines we obtain detections in the 11–16 MHz range. These are the highest signal-to-noise measurements at these frequencies. The peak optical depth of the Cα lines changes considerably over the 11–33 MHz range with the peak optical depth decreasing from 4 × 10−3 at 33 MHz to 2 × 10−3 at 11 MHz, while the linewidth increases from 20 km s−1 to ∼150 km s−1. The combined change in peak optical depth and linewidth results in a roughly constant integrated optical depth.We interpret this as carbon atoms close to local thermodynamic equilibrium. In this work, we focus on how the 11–33 MHz carbon radio recombination lines can be used to determine the gas physical conditions. We find that the ratio of the carbon radio recombination lines to that of the 158 μm [C II] fine-structure line is a good thermometer, while the ratio between low-frequency carbon radio recombination lines provides a good barometer. By combining the temperature and pressure constraints with those derived from the linewidth, we are able to constrain the gas properties (electron temperature and density) and radiation field intensity. Given the 1σ uncertainties in our measurements these are: Te ≈68–98 K, ne ≈0.02–0.035 cm−3 and Tr,100 ≈1500–1650 K. Despite challenging radio frequency interference and ionospheric conditions, our work demonstrates that observations of carbon radio recombination lines in the 10–33 MHz range can provide insight into the gas conditions.